Clinical Aspects of Stevens-Johnson Syndrome/Toxic Epidermal Necrolysis With Severe Ocular Complications in Taiwan - David Hui-Kang Ma (Frontiers in Medicine, 2021)
Purpose: Over the last decade, there has been tremendous progress in the treatment of Stevens-Johnson syndrome (SJS) and toxic epidermal necrolysis (TEN). To understand whether this has resulted in better ophthalmic outcomes, we aimed to study the incidence of severe ocular complications (SOCs) in the acute and chronic stage among SJS/TEN patients, major causative medications, and therapeutic effect of medical and surgical treatment.Methods: Using electronic medical records review of patients of Chang Gung Memorial Hospital Linkou Branch from 2010 to 2020, 119 patients (236 eyes) received ophthalmic consultation during the acute stage and were retrospectively studied. Sotozono's grading score systems for acute and chronic SJS/TEN were employed for accessing correlation between acute and chronic presentations, the therapeutic effect of systemic etanercept treatment, and outcome of early amniotic membrane transplantation (AMT) performed in patients with severe acute SOCs.Results: There were 46 male and 73 female patients with a mean age of 45.6 ± 22.7 years old (2–90 years), and follow-up time of 408.3 ± 351.0 (116–1,336) days. The numbers of patients with SJS, overlap syndrome, and TEN were 87, 9, and 23, respectively. In total, 109 eyes (55 patients) had acute SOCs, which comprised 46.2% of patients who underwent ophthalmic examination. Antiepileptics were the most common category of culprit drugs causing SOCs in the acute stage. At the end of follow-up, there were 14 eyes (9 patients) with chronic SOCs (5.9%), and non-steroidal anti-inflammatory drugs and cold medicine were the most common causative medications that were associated with severe chronic sequela. The correlation between Sotozono's acute and chronic grading score showed a positive relationship [Spearman's rank correlation coefficient (r) = 0.52, p < 0.001]. The average chronic grading scores in patients receiving systemic corticosteroid combined with etanercept treatment were significantly lower than those receiving corticosteroid only, Finally, the average chronic grading scores in patients receiving AMT <7 days after onset were significantly lower than those performed beyond 7 days.Conclusion: Our study implies that acute manifestation can be an indicator for chronic sequelae. Additional early etanercept treatment and early AMT showed beneficial effect in reducing chronic ocular sequela.